CURRENT TENDENCIES IN THE DEVELOPMENT OF METROLOGICAL SUPPLY OF MEASURING INSTRUM - Tairov Baxtiyor Boboqulovich; Shadiyev Suxrob Sadilloyevich; Azimova Firuza Kamolovna (American Journals Publishing, 2023)
Today, the metrological supply of measuring instruments in our country is undergoing major changes. Uzbekistan's new rules for becoming a member of the global trade system will further expand new aspects of export potential. Laws that allow us to raise the competitiveness of our country to a new level are considered very important. A number of main directions for consideration in the field of metrological provision of measuring instruments are presented.
Keywords: Product quality, sensor, transducer, output signal, risk of defects, measuring instruments, terminology, plateau, calibration procedure.